HUBUNGAN PERILAKU IBU MENYUSUI DENGAN MOTIVASI MEMBERIKAN ASI PADA BAYI USIA (0-9 BULAN) DI WILAYAH KERJA PUSKESMAS MAESAN : Relationship Between Breastfeeding Mothers' Behavior and Motivation to Breastfeed Infants (0-9 Months) in The Working Area of The Maesan Community Health Center - Pradana, Yudha Restu Pradana; Hidayat, Cahya Tribagus; Suryaningsih, Yeni (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
The behavior of breastfeeding mothers is a series of actions and skills performed by a mother to provide breast milk to her baby. This study used a descriptive quantitative research design with a cross-sectional method which aims to determine the relationship between the behavior of breastfeeding mothers with breastfeeding motivation in infants aged (0-9 months) in the working area of the Maesan Health Center. The population in this study were breastfeeding mothers who had babies aged 0-9 months, totaling 100 people. The sampling technique used Simple Random Sampling. Assessment using a questionnaire regarding the behavior and motivation of breastfeeding mothers in providing breast milk. The results of the study using the Spearman Rho Rank test (a = 0.05) showed that there was a significant relationship between the behavior of breastfeeding mothers and the motivation to provide breast milk to infants. The results of the research on breastfeeding motivation showed 66.3% good motivation, 26.3% sufficient motivation, and 7.5 lack of motivation. The relationship between breastfeeding behavior of mothers with breastfeeding motivation in infants with the Spearman Rho Rank test obtained a p value of 0.00. The conclusion of this study is that there is a relationship between the behavior of breastfeeding mothers with breastfeeding motivation in infants aged (0-9 months) in the working area of the Puskesmas.